Deepfake culture: the emergence of audio-video deception as an object of social anxiety and regulation. Issue 4 (4th July 2022) - Cover, Rob
ABSTRACT: Deepfakes draw on algorithmic powers, machine learning and modern capabilities for processing information to allow users to insert the face, body, and visual information about a real-world person into a false setting, producing highly convincing videos that appear to be a 'true' record. Emerging on the scene in the past half-decade, deepfake applications have become an object of widespread social concern and calls for regulation, ostensibly to prevent electoral fraud, defamatory misuse, the pornographisation of public figures and to restore a sense of veracity to texts and communication. This paper addresses deepfakes from a cultural studies standpoint, asking what happens if we shift away from perceiving the technology as having a negative impact and, instead, appreciating it as a cultural technology constituted in widespread shifts in the cultural sense of texts, representation, play, co-creativity and pastiche. In doing so, the paper uses cultural theory to address three points: the cultivation of the deepfake in older communication practices, the ways in which it enters public debate as an object of social concern and, finally, how calls for the regulation of deepfake technologies and products misses an opportunity to reassess the cultural ethics of communication.